Hybrid microchannel-solid state micropore device for fast and optical cell detection - Olmos Carreno, Carol Maritza (2020)
This paper presents a methodology for cell detection and counting using a device that combines PDMS (polydimethylsiloxane) microfluidic multilayer channels with a single solid state micropore. Optimal conditions of solid-state micropore fabrication from crystalline silicon wafers are presented. Micropores of varying size can be obtained by directly etching using an etchant agent concentration of 50 wt% KOH, at varying temperatures (40, 60, 80 °C) and voltages (100, 500, 1000 mV). Scanning Electron Microscopy (SEM), and profilometry techniques have been used for the micropore characterization. In order to find optimal conditions for cell detection a COMSOL Multiphysics simulation was performed. Pressure drop, shear stress, fluid viscosities and flow rates parameters were evaluated. The potential viability of the device for cell detection and counting, avoiding cellular damage, is demonstrated.